Removal Of Dimethoate, Carbendazim And Chlorpyrifos Residues From Date Fruits And Evaluation Of The Treatments Effect On The Nutrition Value - Ali, Ahmeda. Kalefa; Zanariah C. W; Mohd Sukri.H (Asian Scholars Network, 2024)
Vol. 2, No. 2 (Pg 85-102)